Identification of Anticancer and Antioxidant Potentials of Katang-Katang Flower Extract (Ipomea pes-caprae Linn) with Water Solvent - Tamuddin, Yusriadi; Utami, Hermin Hardyanti; Husna, Saadatul; Lestari, Mega Fia; Salawali, Rismul Trianto; Towolioe, Sherly; Aras, Neny Rasnyanti M; Trifany, Andi Wahyu; Papriani, Nada Pertiwi (Hasanuddin University, 2023)
Cancer is a group of deadly diseases that attack human organs with an increasing number of cases and an increasing number of deaths from year to year. Free radicals as unstable molecules are one of the triggers for the emergence of cancer. Katang-katang or I. pes-caprae L. is a plant that could be found on almost all tropical coasts. So it has the potential to be developed as herbal medicine. This study used Flowers of I. pes-caprae L. as the research sample. This study aimed to identify the anticancer and antioxidant potential of the flower extract of I. pes-caprae L extracted with water as a solvent. This research included the phytochemical test of secondary metabolites, identification of anticancer potential based on the toxicity test using the Brine Shrimp Lethality Test (BSLT), and the antioxidant activity test using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The results showed that the flower extract of I. pes-caprae L. from water solvent contained active compounds including alkaloids, flavonoids, tannins, saponins, and terpenoids. The extract also has the potential as an anticancer with an LC50 value of 170.8441 ppm and strong antioxidant activity with an IC50 value of 71.7895 ppm.